Macrophages promote epithelial repair through hepatocyte growth factor secretion. (8th September 2013) - D'Angelo, F.; Bernasconi, E.; Schäfer, M.; Moyat, M.; Michetti, P.; Maillard, M. H.; Velin, D.
Summary Macrophages play a critical role in intestinal wound repair. However, the mechanisms of macrophage‐assisted wound repair remain poorly understood. We aimed to characterize more clearly the repair activities of murine and human macrophages. Murine macrophages were differentiated from bone marrow cells and human macrophages from monocytes isolated from peripheral blood mononuclear cells of healthy donors (HD) or Crohn's disease (CD) patients or isolated from the intestinal mucosa of HD. In‐vitro models were used to study the repair activities of macrophages. We found that murine and human macrophages were both able to promote epithelial repair in vitro. This function was mainly cell contact‐independent and relied upon the production of soluble factors such as the hepatocyte growth factor (HGF). Indeed, HGF‐silenced macrophages were less capable of promoting epithelial repair than control macrophages. Remarkably, macrophages from CD patients produced less HGF than their HD counterparts (HGF level: 84 ± 27 pg/mg of protein and 45 ± 34 pg/mg of protein, respectively, for HD and CD macrophages, P < 0·009) and were deficient in promoting epithelial repair (repairing activity: 90·1 ± 4·6 and 75·8 ± 8·3, respectively, for HD and CD macrophages, P < 0·0005). In conclusion, we provide evidence that macrophages act on wounded epithelial cells to promote epithelial repair through the secretion of HGF. The deficiency of CD macrophages to secrete HGF and to promote epithelial repair might contribute to the impaired intestinal mucosal healing in CD patients.